A bizarre new species of Lynchius (Amphibia, Anura, Strabomantidae) from the Andes of Ecuador and first report of Lynchius parkeri in Ecuador - Sánchez-Nivicela, Juan C.; Urgiles, Veronica L.; Navarrete, María José; Yánez-Muñoz, Mario H.; Ron, Santiago (Zootaxa, 2019)
We describe a new species of Lynchius from the eastern montane forest of southern Ecuador. We also report the occurrence of L. parkeri in Ecuador, on paramos of Yacuri National Park, near the border with Peru. We used morphological and genetic evidence for the description of the new species and the new report of L. parkeri. Phylogenetic analyses were carried out using both maximum likelihood and Bayesian inference on DNA sequences for mitochondrial and nuclear genes. The phylogeny shows that L. simmonsi is sister to a clade composed of the remaining species of Lynchius and that the new species is sister to L. flavomaculatus. The new species has a prominent and heavily ossified head with noticeably spiculate cranial exostosis that easily distinguishes it from all its congeners. The dorsal region and limbs present several reduced subconical and rounded tubercles and pronounced dermal ridges on the dorsum. We also describe the osteology of the new species based on x-rays of the holotype. Only six species of Lynchius, two known to occur in Ecuador (L. flavomaculatus and L. simmonsi). The description of L. megacephalus sp. n. and new record of L. parkeri double the number of known Lynchius in Ecuador and suggest that the diversity of Ecuadorian and Peruvian Lynchius is still underestimated.